2020
DOI: 10.1016/j.techsoc.2020.101431
|View full text |Cite
|
Sign up to set email alerts
|

Automation fears: Drivers and solutions

Abstract: New technologies offer employers the ability to replace tasks done by human labour with those done by machines. There are challenges for both employers and employees, as employers look for strategies for the implementation of automation technologies and employees may have concerns about their employment being threatened by automation technologies. In this research, we analyse data of over 500 Bulgarians to learn about how they perceive the automation of their job. The analysis finds that there are segments of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 61 publications
(45 reference statements)
1
20
0
1
Order By: Relevance
“…Sin duda alguna la implantación de nuevas TI requieren contar con nuevas habilidades de los miembros de las entidades (Ivanov et al, 2020), por otra parte, Kozak et al (2020) mencionan que la incertidumbre de reemplazar la mano de obra por estas tecnologías obstaculiza la automatización de los procesos empresariales, afectando a la productividad.…”
Section: Resultados De La Revisiónunclassified
“…Sin duda alguna la implantación de nuevas TI requieren contar con nuevas habilidades de los miembros de las entidades (Ivanov et al, 2020), por otra parte, Kozak et al (2020) mencionan que la incertidumbre de reemplazar la mano de obra por estas tecnologías obstaculiza la automatización de los procesos empresariales, afectando a la productividad.…”
Section: Resultados De La Revisiónunclassified
“…From this perspective, it is worth noting that the phenomena and processes related to automation cause transformations within companies and other institutions, related to areas of employment, human resource management and education [36]. As noted in numerous works [37][38][39][40][41], automation is a huge challenge for whole societies, because it forces changes in companies in terms of production processes, as well as operating principles, organizational models and information methods to build sensitive solutions based on innovation. This results in the need to adapt the entire labor market and education systems [36] in order to minimize the negative social impact of automation [42], improve skills [43] and professional flexibility [44] and build and support the competitiveness of emerging smart businesses of the future [45,46].…”
Section: Polish Mining In the Context Of Changes Resulting From Revolution 40 And The Knowledge-based Economymentioning
confidence: 99%
“…Spencer [38] questions whether work will actually be reduced by technological progress and argues that the threat workers associated with technological progress mainly comes from the erosion in the quality of work rather than from the loss of work. This notion is underlined by a study from Bulgaria, that identified the attitudes towards the dehumanizing effects of automation, peer-pressure, and the individual self-perception of workers as being the main drivers of the fear of automation [39]. Similar concerns are raised by Fleming [33] and Gallie [40]; who suggest that the broad application of digital technologies might eventually lead to intensified work and managerial control or even surveillance in highly automated companies.…”
Section: Industry 40 and Industrial Employmentmentioning
confidence: 93%